Advances in mergers and acquisitions. Vol. 14 - Cooper, Cary L.; Finkelstein, Sydney (Emerald, 2015)
As a number of Western economies begin to emerge from the shadows of recession, the level of merger and acquisition activity has picked up dramatically. Although CEOs predict synergies in mapping out a merger or acquisition, the reality is far from the rhetoric. The Advances in mergers and acquisitions series is in its 14th year, and research in this field continues to grow, and help highlight the inhibitors and enhancers for successful M & As. These ten chapters explore sequential aspects of the M & A process, from the pre-combination phase, to issues that should be taken into account when considering a merger or acquisition, to post-merger integration concerning the determinants of acquisition performance. Contributing authors: Fadi Alkarraan, Nima Amiryany, Terrill Frantz, John Howard, Jochem T. Hummel, Alexei Koveshnikov, Rebecca Lund, Sigmar Malvezzi, Kenneth Marks, Mitchell Marks, Katty Marmemout, Muriel Mignerat, Phillip Mirvis, Ladislau Nascimento, Kamal Ghosh Ray, Sangita Ghosh Ray, Janne Tienari.
Keywords: Business & Economics -- Strategic Planning.; Business strategy.; Consolidation and merger of corporations.; elektronické knihy; electronic books